Evaluasi Potensi Gas Rumah Kaca Berdasarkan Sektor Ketenagalistrikan dan Infrastrukur Penyediaan Air Minum di Kota Batam - Yosef Adicita; Nurul Ulfah; Sri Dewi Handayani; I Wayan Koko Suryawan (Matriks Teknik Sipil, 2021)
Batam City is one of the biggest city in Indonesia. The economic development in Batam City is increasing, which is followed by the needs of the city. Electricity and water supply requirements are one of the essential aspects of the management of a city and sustainable development. Electricity consumption and water supply can contain carbon dioxide (CO2) emissions. The purpose of this study is to estimated CO2 emissions in Batam City from electricity activity and water consumption.Calculation of carbon dioxide emissions from electricity consumption in Batam uses an emission factor of 0.975 tons CO2/MWh, while for water supply consumption uses an emission factor of 0.51 kgCO2/m3. Projections are carried out until 2030 in accordance with sustainable development goals. Based on electricity consumption, the highest contributor to emissions in 2014-2017 is the business sector with the highest value of 679,658 tons of CO2. Emissions from electricity consumption from the industrial sector fell from 567,904 tons of CO2 in 2014 to 510,630 tons of CO2 in 2017. The projected emissions that will emit emissions from the industrial sector will increase each year. Water consumption showed the highest emissions in the household sector at 28.461 tons of CO2 in 2017. Compared with the projected results on water supply, only 2.21% compared to total electricity consumption emissions.